Phenotyping patient-reported health profiles in octogenarians with coronary artery disease – a latent profile analysis. (3rd October 2022) - Instenes, I; Breivik, K; Allore, H; Borregaard, B; Deaton, C; Larsen, A I; Wentzel-Larsen, T; Norekval, T M
Abstract: Background: Percutaneous coronary intervention (PCI) has demonstrated to be an effective treatment strategy also in octogenarian patients (≥80 years). However, limited studies describe patient-reported outcomes in older adults two months after the PCI procedure. Purpose: To identify latent health profiles concerning fatigue, generic and disease-specific physical and mental health, anxiety and depression, insecurity, dependency and angina frequency. Further, to investigate if these profiles were associated with sex or cohabitation status. Method: A prospective cohort multicenter study including 3417 patients was conducted. The following patient-reported outcome measures were used: Level of fatigue was assessed using de novo created questions. Generic physical and mental health was assessed using RAND-12. Anxiety and depression were assessed using the Hospital Anxiety and Depression Scale. Disease-specific physical and mental health status, insecurity and dependency were assessed with Myocardial Infarction Dimensional Assessment Scale, and disease-specific physical limitation, quality of life and angina frequency was assessed with Seattle Angina Questionnaire (SAQ-7). All scales were converted to a 0–100 scale (worst to best). Latent profile analysis was used for phenotyping health profiles and multinomial logistic regression analysis for investigating the association of sex and cohabitation status across health profiles. Result: A total of 318 octogenarians were included. The mean age was 83.6 years, and 69% were males. Three health profiles differing in the level of fatigue, health status, insecurity and dependency and angina frequency were identified (Figure 1). Health profile 1 (26.1%) represents "Low-level of life satisfaction, high level of insecurity and dependency and monthly frequency of angina". Health profile 2 (38.1%) represents "Medium-level of life satisfaction, medium-level of insecurity and dependency and monthly frequency of angina". Health profile 3 (35.8%) represents "High-level of life satisfaction, low level of insecurity and dependency and angina free". Importantly, female sex was strongly associated with being classified into Health profile 1 compared to Health profile 3 [OR 3.6, 95% CI 1.3–7.9]. Living alone however, did not predict a likelihood of being classified into any particular health profile. Conclusion: We identified three unique health profiles of octogenarians with coronary artery disease. A quarter of the participants were classified into the "Low-level of life satisfaction" profile. In addition, female sex was strongly associated with being identified into the "Low-level of life satisfaction" profile. These result suggest a need for a more tailored and patient-centered aftercare in octogenarians undergoing PCI. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): MTG Holding AS